PREGNANT WOMEN'S NUTRITIONAL STATUS - Enok Nurliawati; Etty Komariah; Eka Widianing Astuti (Journal of Maternity Care and Reproductive Health, 2020)
The research was based on pregnant women who experienced malnutrition in the  PHC of Tamansari, Tasikmalaya. Malnutrition on pregnant women causes interference to maternal and fetal health. Malnutrition can be anticipated by conducting screening in pregnant women so that it can be immediately identified and immediately addressed. This study aimed to identify the nutritional status based on upper arm circumference, BMI, and body weight gain based on BMI. The type of research was a quantitative descriptive. The sampling technique used stratified random sampling, the number of samples were 89 people. The study was conducted in the area of Tamansari  PHC  Data collection used weight scales, microtome stature meter, upper arm circumference, and body weight before pregnancy was taken secondary from the MCH book.  The results showed that majority of the respondents based on upper arm circumference were 66  people (74.2%) who did not experience malnutrition, based on BMI  49 people (55.1%) were normal, and based on body weight, 43 respondents (48.3%) were categorized as overweight according to gestational age. This research can be used as a basis for health promotion information regarding the nutritional status and further research needs to be done related to the impact of malnutrition and excess nutrition.Keywords: Pregnancy, malnutrition, nutritional status.